Síntese de ésteres graxos de açúcar catalisada por derivados imobilizados-estabilizados de candida antarctica lipase B - Gonçalves, Maria Carolina Pereira (Universidade Federal de São Carlos, 2023)
The biotechnology industry is increasingly seeking to deploy high productivity and stable biocatalysts for commercial-scale production of bioproducts. In addition, with global warming, enzyme-based production systems using renewable feedstocks are aligned with the principles of sustainability and green chemistry. Considering this perspective, sugar fatty acid esters (SFAEs) have great potential for industrial use as high value bioproducts. These non-ionic surfactants are widely used in detergents, oral hygiene products, food, cosmetics, and the pharmaceutical industry. They are usually synthesized from the esterification of sugars and fatty acids in the presence of chemical catalysts. Nonetheless, this approach requires high energy consume and presents low selectivity, turning the products separation/purification steps costly. As an alternative, the enzymatic synthesis of SFAEs has been studied. In this thesis, we used principles of systematic mapping to write two literature reviews, the first covering research on the synthesis of SFAEs with Candida antarctica lipase B (CALB), and the second covering research on the production and recovery of sugars from lignocellulosics to synthesize bioproducts (mostly xylose-derived products). Then, we performed the synthesis of xylose oleate in methyl ethyl ketone (MEK) catalyzed by the Lipozyme® 435/Novozyme® 435 (L435/N435, commercial CALB immobilized on an acrylic resin). Results showed that an excess of oleic acid significantly favored the reaction. The predicted Ping Pong Bi Bi kinetic model fitted to the experimental data and there was no evidence of inhibitions in the range assessed. The L435 repeated use showed a reduction of 48 and 19% in the xylose and oleic acid conversions, respectively, after 10 12h-cycles. This significant decrease in the conversions mainly occurred due to the CALB desorption from the support in the presence of our reaction product. In an attempt to minimize this issue, the next step consisted of the L435 coating with polyethyleneimine (PEI) for use as biocatalyst in the synthesis of xylose laurate/palmitate in MEK. The L435 treatment with 2 KDa PEI prevented the enzyme leakage in the crude sugar ester product and produced the highest enzyme stability in different media (MEK and buffer solutions at different pHs), besides affording a higher xylose modification degree than the uncoated enzyme. After 5 6 h-reuse cycles with the PEI-coated L435, the xylose conversions only decreased by 10%, while with the non-treated biocatalyst they decreased by 37%. At last, the synthesis of SFAEs from lignocellulosic biomass and oleic acid was catalyzed by the uncoated and PEI-coated N435 in MEK medium. After steam-explosion pretreatment of mixed hardwoods and high solids enzymatic hydrolysis at 15%wt solids, the hydrolysate extract was purified and concentrated to a xylose/glucose mass ratio of ~3 to 1. These lignocellulosic sugars were superior to the same commercial sugars as the carbohydrate source for the esterification reaction in terms of sugar conversions. Coating the N435 with PEI prevented enzyme leakage into the reaction medium and produced 35% and 50% higher xylose and glucose conversions to SFAEs, respectively. After 6 24 h-reuse cycles with the PEI-coated N435, the xylose conversion decreased by 44%, while a 65% reduction was observed with the uncoated lipase. In the first two studies, mass spectrometry analysis confirmed the formation of xylose mono-, di-, and tri- esters. In this last one, only xylose and glucose mono- and di- esters were found. In all cases our purified product presented an emulsion capacity close to that of a commercial sugar ester.
Synthesis of sugar fatty acid esters catalyzed by immobilized-stabilized derivatives of candida antarctica lipase B
Keywords: Ésteres graxos de xilose; Biomassa lignocelulósica; Ácidos graxos; Metil etil cetona; Lipases imobilizadas; Xylose fatty acid esters; Lignocellulosic biomass; Fatty acids; Methyl ethyl ketone; Immobilized lipases; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA